2005
DOI: 10.1128/iai.73.1.649-651.2005
|View full text |Cite
|
Sign up to set email alerts
|

Babesia divergensandPlasmodium falciparumUse Common Receptors, Glycophorins A and B, To Invade the Human Red Blood Cell

Abstract: Babesiosis has long been recognized as an economically important disease of cattle, but only in the last 30 years has Babesia been recognized as an important pathogen in humans. Invasion of erythrocytes is an integral part of the Babesia life cycle. However, very little information is available on the molecules involved in this process, in contrast to another hemoparasite, Plasmodium falciparum. Using invasion assays into normal red blood cells (RBCs), enzyme-treated cells, and clinically mutant cells, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…The identity of the RBC receptor remains to be shown; however, due to the neuraminidase resistance of the binding profile, the sialic acid residues on the major sialo-glycoproteins molecules on the red cell, namely, the glycophorins A, B and C, can be ruled out as the cognate receptor for BdAMA1. Earlier, we had shown that glycophorins A and B function as invasion receptors (22) for the B. divergens merozoite, but clearly the sialic acid moieties on them are not involved in the interaction of BdAMA1 with the RBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identity of the RBC receptor remains to be shown; however, due to the neuraminidase resistance of the binding profile, the sialic acid residues on the major sialo-glycoproteins molecules on the red cell, namely, the glycophorins A, B and C, can be ruled out as the cognate receptor for BdAMA1. Earlier, we had shown that glycophorins A and B function as invasion receptors (22) for the B. divergens merozoite, but clearly the sialic acid moieties on them are not involved in the interaction of BdAMA1 with the RBC.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 0.2 ml of packed RBCs was treated with either 2 ml of a 1 mg/ml concentration of trypsin (treated with tosylsulfonyl phenylalanyl chloromethyl ketone; Sigma), 1 ml of a 1 mg/ml concentration of chymotrypsin (Sigma), or 0.1 ml of a 0.1 IU/ml concentration of neuraminidase (Sigma) for 30 min at 37°C. Cells treated with trypsin were then washed and treated with 0.5 mg/ml soybean trypsin inhibitor (Sigma) for 15 min at room temperature, as described earlier (22). The efficacy of each enzyme treatment was assessed in the Laboratory of Immunohematology, New York Blood Center, by assaying for the loss of RBC agglutinability using a panel of monoclonal antibodies against suitable antigenic determinants on different blood group proteins.…”
Section: Rbc Binding Assays (I) Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the molecular interactions between Babesia parasites and their receptors on the bovine host cell surface (Lobo 2005). Cattle infected with B. bigemina and B. bovis present clinical signs very similar to those of human beings infected with Plasmodium vivax and Plasmodium falciparum (Cooke et al 2005).…”
mentioning
confidence: 99%
“…The genera Babesia and Plasmodium belong to phylum Apicomplexa and present similar features such as invasion of host cells (Taylor et al 1990, Dubremetz 1998, Menard 2001, Cowman & Crabb 2006, which demands an interaction between a speciϐic receptor on the vertebrate red blood cell (RBC) membrane and a ligand on the parasite surface (Lobo 2005, Yokoyama 2006. Little is known about the molecular interactions between Babesia parasites and their receptors on the bovine host cell surface (Lobo 2005).…”
mentioning
confidence: 99%